A late complication of pectus excavatum repair. Issue 800 (June 1992) - McWilliams, R.; Hooper, T.; Lawson, R.
Abstract : We report a late complication of pectus excavatum repair which highlights the importance of a chest X-ray in evaluating chest pain in patients who have had previous chest surgery. It also raises the question of whether or not implanted wires should be electively removed following bony union.